Urban enemies : a collection of urban fantasy stories from Kelley Armstrong, Jim Butcher, Domino Finn, Diana Pharaoh Francis, Kevin Hearne, Faith Hunter, Caitlin Kittredge, Jonathan Maberry, Seanan McGuire, Jon F. Merz, Joseph Nassise, Lilith Saintcrow, Steven Savile, Craig Schaefer, Jeff Somers, Carrie Vaughn, Sam Witt - Nassise, Joseph; Butcher, Jim, 1971-; Armstrong, Kelley; Somers, Jeff, 1971-; Schaefer, Craig (Fantasy fiction writer); Saintcrow, Lilith; Hearne, Kevin; Kittredge, Caitlin; Nassise, Joseph; Vaughn, Carrie; Maberry, Jonathan (Gallery Books, 2017)
"Villains have all the fun--everyone knows that--and this anthology takes you on a wild ride through the dark side! The top villains from seventeen urban fantasy series get their own stories--including the baddies of New York Times bestselling authors Jim Butcher, Kevin Hearne, Kelley Armstrong, Seanan McGuire, and Jonathan Maberry. For every hero trying to save the world, there's a villain trying to tear it all down. In this can't-miss anthology edited by Joseph Nassise (The Templar Chronicles), you get to plot world domination with the best of the evildoers we love to hate! This outstanding collection brings you stories told from the villains' point of view, imparting a fresh and unique take on the evil masterminds, wicked witches, and infernal personalities that skulk in the pages of today's most popular series. The full anthology features stories by Jim Butcher (the Dresden Files), Kelley Armstrong (Cainsville), Seanan McGuire (October Daye), Kevin Hearne (The Iron Druid Chronicles), Jonathan Maberry (Joe Ledger), Lilith Saintcrow (Jill Kismet), Carrie Vaughn (Kitty Norville), Joseph Nassise (Templar Chronicles), Domino Finn (Black Magic Outlaw), Steven Savile (Glasstown), Caitlin Kittredge (Hellhound Chronicles), Jeffrey Somers (The Ustari Cycle), Sam Witt (Pitchfork County), Craig Schaefer (Daniel Faust), Jon F. Merz (Lawson Vampire), Faith Hunter (Jane Yellowrock), and Diana Pharaoh Francis (Horngate Witches)"--